DO POLITICALLY CONNECTED BANKS PERFORM BETTER IN A DEMOCRATIC ENVIRONMENT? - Hasan, Rashedul; Hassan, Mohammad Kabir; Tian, Jiayuan (Bank Indonesia, 2024)
This paper elucidates the intricate relationship among bank performance, political connections, and the democratic environment. The existing body of evidence is notably limited in illustrating the impact of a democratic environment on bank performance. Our study examines a sample of 397 banks spanning 14 countries and districts, encompassing both politically affiliated and non-politically affiliated banks in both democratic and non-democratic settings. The empirical findings reveal a reduction in non-performing loans but an escalation in loan loss provision within a democratic environment. This phenomenon may be attributed to the diminished level of financial constraints prevalent in democratic settings. Furthermore, our investigation revealsthat political connections exert a deleterious effect on the non-performing loans (NPL) ratio, coupled with a salutary impact on loan loss provision. Conclusively, our research identifies that the stock return of politically connected banks in democratic environments is inferior to their counterparts in non-democratic environments. Additionally, the non-performing loans ratio (NPL) of politically connected banks in democratic environments tends to be higher compared to their non-democratic counterparts. Conversely, the loan loss provision of politically connected banks in democratic environments tends to be lower than that in non-democratic environments. This nuanced analysis contributes to a more comprehensive understanding of the interplay between democratic environments, political connections, and bank performance.